Analisis dan Perancangan Sistem Informasi Perpustakaan Sma Negeri Xyz - Titan Titan; Devyano Luhukay; Yohannes Kurniawan (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Library information system analysis and design for public senior high school XYZ in South Tangerang aims to identify needs of data and information about library operational transaction in the school. The result of requirement analysis was used to build a computerized system supporting the run of library business process. The analysis and design focused on solving the problems, such difficulties in finding book location, book availability, and else. Rational Unified Process was used for the information system development methodology and the result of requirement analysis was documented by using unified modeling language; user interface was also designed. This information system was expected to ease the library in doing its activity by serving the information related to book searching, book availability, book tracking. Besides, it would also fasten the process of book borrowing, book returning, and new book registration.